PSM & PTA evaluation system using PDA (PPESUP) - Irman Agoes, Mohd Simin (2010)
Today almost all the evaluation system is using form to perform the evaluation process.Nowadays,with the technology era is expanding, this method appeared to be no longer suitable and systematic.There are many weaknesses in today system for example the loss of form,unreadable or misread of evaluator handwriting and most of all record are stored manually.Thus,this system is build to override the manual system to become a computerized system.PSM & PTA EVALUATION SYSTEM USING PDA (PPESUP) is focused on building a system where evaluator can evaluate by using PDA and this project also focused in computerizing the method of evaluation to become more systematic.The new system can reduce the problems that occur on the old method and can ease the workload of the manager in storing all the purchase record.Web based technique are used during the implementation of the system to enable access to the system through web surfer.in addition,PUP languages and MySQL database are used appropriate with the system functionality.